Чорногорська мова сьогодні: соціолінгвістичний статус, проблема норми - Васильєва, Л.П. (Мовознавство, 2011)
Надання статусу офіційної чорногорській мові пов’язують з отриманням Чорногорією
статусу незалежної держави. Для вирішення мовних питань у державі 2008 р. створено Раду з
питань стандартизації. В «Офіційному кур’єрі» за сприяння Міністерства освіти і науки
Чорногорії вийшов друком правопис чорногорської мови, де знайшла відображення низка її
специфічних ознак. Проте до сьогодні в країні фактично функціонує дві мови: сербська і
чорногорська. With the Serbo-Croatian language getting out of use, the rise of four language standards is both natural and regular process. The standards are genetically correlative with the Shtokavian dialects. Granting the status of official to the Montenegrin language is connected with obtaining by Montenegro of the status of an independent state. The «Council on Language Standardization» was founded in 2008 to solve language matters. With the Montenegrin Ministry of Education and Science’s assistance the orthography of the Montenegrin language has been published in the Official Courier off the Montenegrin power, where a number of its specific features has been reflected. However, up till now two languages — Serbian and Montenegrin—have been functioning in the country.